PENGARUH SUPERVISE KLINIS DAN SUPERVISE AKADEMIK KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMP NEGERI 3 RAMBANG DANGKU KABUPATEN MUARA ENIM - Oktarina Tamar; Yasir Arafat; Mulyadi Mulyadi (STKIP Pesisir Selatan, 2020)
This study describes the effect of clinical supervision and academic supervision of principals on teacher performance in state junior high school 3 Rambang Dangku Muara Enim Regency. This study uses quantitative methods. Techniques and data collection procedures through questionnaires, observation, and documentation. Data were analyzed using multiple linear regression. Based on the data analysis, the conclusion is 1) there is a clue to clinical supervision of teacher performance, meaning that clinical supervision can renew teacher performance. 2) There is an effect of principal academic supervision on teacher performance. 3) there are clinical supervision and academic supervision of principals on teacher performance, thus teaching skills and work motivation collectively on teacher performance. Clinical supervision and academic supervision of principals are able to affect teacher performance with a contribution of 24.1%